ORIENTASI PERCAKAPAN SUKU MELAYU BAJAU KUALA TUNGGKAL JAMBI: SUATU KAJIAN ANTROPOLINGUISTIK - FITRAH, H. YUNDI (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 14 (2007): September 2007, 2007)
Abstract This writing describes the orientation of Melayu Bajau Jambi ethnic conversation; it is a study on anthropology of the conversation, including (1) conservative conversation which refers to the unlucky fate in the past dependent on superior (2) transitional conversation about good things, status and honor at present, harmonious relation with nature and fellow beings, and (3) the conversation leading to the difficulty, challenge for better future life based on self reliance. The result of the conversation orientation about the essence of life was conservative leading to the unfortunate of the past, dependent on the superior. The orientation of conservation about the essence of work, and time is still conservative dependent on the nature. Although they have much money, they do not save it in a bank or for education . They tend to be consumptive instead. The orientation of conversation related to the relationship between human being and nature is also still conservative. However, the relationship on the ecosystem of nature tends to be in transistion and the orientation seems to be adaptive to nature. The orientation of conservation about the essence of relationship among fellow beings the same creature tends to be transitional. The existence of formal institutions can improve economy and democracy. Kata-kata kunci: Onentasi percakapan Bahasa Melayu bajau Jambi dan Hubungannya dengan hakikat hidup